Vehicle ride performance with semi-active suspension system using modified skyhook algorithm and current generator model - Abu Bakar, Saiful Anuar (Inderscience Publishers, 2008)

(untitled)
This paper presents the simulation of a semi-active suspension system by using designed parameter model of magnetorheological (MR) damper. The design is based on the performance of the original equipment shock absorber of a passenger vehicle. A 7DOF of vehicle ride model was developed and validated in order to study the performance of a passive suspension system and the designed semi active suspension system. A controller known as modified skyhook algorithm and current generator model was used in the semi-active suspension system. The simulation results show that the semi active suspension system give significant improvement on vehicle's ride comfort.